Passivity Without Reference. Salomon Maimon’s Contribution to the Development of Idealism - Herrera, Hugo Eduardo (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This article approaches Salomon Maimon’s contribution to critical philosophy in terms of the issue of passiveness or receptiveness of knowledge. Maimon tries to reinterpret the notions of the thing in itself and of the given within the framework of criticism, in such a way that they do not refer to a transcendence that is directly unattainable by knowledge. In this attempt, to a certain extent he incorporates the given into subjectivity and tries to explain it on the basis of the action of constitutive understanding. With this, he triggers the passage from transcendental Kantian philosophy to the idealism of Fichte. Nonetheless, his position faces the subsequent problem of explaining how the constitution of the given from understanding (infinite) can become compatible with the criticism it takes on
Keywords: criticism; receptivity; reference; purely conceptual knowledge; infinite understanding